2011
DOI: 10.1017/s0950268811001294
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of metallo-β-lactamase IMP-14 and VIM-2 inPseudomonas aeruginosaclinical isolates from a tertiary-level hospital in Thailand

Abstract: Seventy-five clinical isolates of Pseudomonas aeruginosa collected in a tertiary teaching hospital in Thailand were investigated for susceptibility to antimicrobials including imipenem. Metallo-β-lactamase (MBL) enzymes were detected by E-test MBL assay and PCR; class 1 integron genes were also detected by PCR. Strains positive for bla(IMP) and bla(VIM) genes were further characterized by DNA sequencing and examined for clonality by pulsed-field gel electrophoresis. High rates of resistance to anti-pseudomonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…These data suggest that OXA-10 and VEB-1 are encoded by a gene located on a mobile element, such as a class 1 integron (Sanschagrin et al, 1995;Girlich et al, 2002;Strateva and Yordanov, 2009). We found that 32.00% of the class 1 integrons of 75 isolates in a study by Piyakul et al (2012) were also present in the clinical isolates in the current study. However, this study did not investigate other mechanisms that may be responsible for resistance to β-lactam such as the alteration or loss of porin protein, or the upregulation of efflux systems.…”
Section: Discussionsupporting
confidence: 54%
“…These data suggest that OXA-10 and VEB-1 are encoded by a gene located on a mobile element, such as a class 1 integron (Sanschagrin et al, 1995;Girlich et al, 2002;Strateva and Yordanov, 2009). We found that 32.00% of the class 1 integrons of 75 isolates in a study by Piyakul et al (2012) were also present in the clinical isolates in the current study. However, this study did not investigate other mechanisms that may be responsible for resistance to β-lactam such as the alteration or loss of porin protein, or the upregulation of efflux systems.…”
Section: Discussionsupporting
confidence: 54%
“…To date, bla IMP-14 has not been described in E. coli , to our knowledge, and has largely previously been reported in P. aeruginosa and Acinetobacter baumannii strains by several hospital centers in Thailand, in some cases as part of clonal outbreaks ( 22 25 ). Although bla IMP-14 is similarly associated with class 1 integrons in these cases, as in pEC732-IMP14, the wider plasmid contexts and sequences of these integrons in P. aeruginosa and A. baumannii strains have not been investigated.…”
Section: Textmentioning
confidence: 90%
“…Recalcitrant P. aeruginosa infection remains a huge threat to public healthcare. Increasing numbers of metallo-β-lactamase-producing clinical isolates have been identified around the world (Corvec et al, 2006 ; Chin et al, 2011 ; Jovcic et al, 2011 ; Piyakul et al, 2012 ; Van der Bij et al, 2012 ), and strains exhibiting resistance to colistin, a “last hope” antibiotic, have also been isolated (Lee et al, 2014 ). Therefore, novel anti-Pseudomonas strategies that do not generate escape mutants are required.…”
Section: Discussionmentioning
confidence: 99%